Multimodal imaging techniques in Yttrium-90 radioembolization for hepatocellular carcinoma: a modality-oriented clinical review - Yang, Tingting; Zhang, Lijie; Xu, Wei; Zheng, Chuansheng; Liang, Bin (Frontiers in Oncology, 2026)
Hepatocellular carcinoma (HCC) is one of the most common malignancies with high global mortality. Yttrium-90 selective internal radiation therapy (90Y-SIRT) is a precision radio-interventional treatment whose efficacy and safety critically depend on accurate microsphere delivery and dose distribution. This review provides an overview of imaging techniques used in 90Y-SIRT, emphasizing both single-modality and multimodal approaches. We summarize the clinical value of ultrasound, CT, MRI, angiography, and nuclear medicine, each providing anatomical, functional, or metabolic information. We further discuss multimodal imaging integration across the treatment workflow: pre-procedural fusion supports patient selection and dose planning; intraprocedural volumetric imaging guides catheter placement; and post-treatment functional imaging assesses microsphere distribution and therapeutic response. By consolidating current evidence, this review highlights the clinical utility of multimodal imaging and identifies areas for optimization in treatment planning, procedural guidance, and outcome assessment of 90Y-SIRT. This synthesis serves as a practical reference for clinicians and researchers aiming to improve the precision and effectiveness of radioembolization for HCC.